The mindfulness diet : eat in the 'now' and be the perfect weight for life - with mindfulness practices and 70 recipes /: eat in the 'now' and be the perfect weight for life - with mindfulness practices and 70 recipes. (2015) - Collard, Patrizia; Stephenson, Helen
No abstract available